Spontaneous activities in baroreflex afferent pathway contribute dominant role in parasympathetic neurocontrol of blood pressure regulation. (25th July 2018) - Xu, Wen‐Xiao; Yu, Jin‐Ling; Feng, Yan; Yan, Qiu‐Xin; Li, Xin‐Yu; Li, Ying; Liu, Zhuo; Wang, Di; Sun, Xun; Li, Ke‐Xin; Wang, Lu‐Qi; Qiao, Guo‐Fen; et al.
Abstract: Aim: To study the dominant role of parasympathetic inputs at cellular level of baroreflex afferent pathway and underlying mechanism in neurocontrol of blood pressure regulation. Methods: Whole‐cell patch‐clamp and animal study were conducted. Results: For the first time, we demonstrated the spontaneous activities from resting membrane potential in myelinated A‐ and Ah‐type baroreceptor neurons (BRNs, the 1st‐order), but not in unmyelinated C‐types, using vagus‐nodose slice of adult female rats. These data were further supported by the notion that the spontaneous synaptic currents could only be seen in the pharmacologically and electrophysiologically defined myelinated A‐ and Ah‐type baroreceptive neurons (the 2nd‐order) of NTS using brainstem slice of adult female rats. The greater frequency and the larger amplitude of the spontaneous excitatory postsynaptic currents (EPSCs) compared with the inhibitory postsynaptic currents (IPSCs) were only observed in Ah‐types. The ratio of EPSCs:IPSCs was estimated at 3:1 and higher. These results confirmed that the afferent‐specific spontaneous activities were generated from baroreflex afferent pathway in female‐specific subpopulation of myelinated Ah‐type BRNs in nodose and baroreceptive neurons in NTS, which provided a novel insight into the dominant role of sex‐specific baroreflex‐evoked parasympathetic drives in retaining a stable and lower blood pressure status in healthy subjects, particularly in females. Conclusion: The data from current investigations establish a new concept for the role of Ah‐type baroreceptor/baroreceptive neurons in controlling blood pressure stability and provide a new pathway for pharmacological intervention for hypertension and cardiovascular diseases.